Practicum Supervision: What Students Need to Know and What Supervisors Ought to Know - Peetoom, Jenny; Nuttgens, Simon A. (Canadian Journal of Counselling and Psychotherapy, 2019)
When graduate-level counselling students begin their practicums, they are often new to both counselling and the practice of supervision. In many instances, students arrive at their practicums with a limited understanding of supervision and how it ought to be carried out; this deficit, we contend, is to their detriment. The premise of this article is that a successful practicum rests on a successful supervisory experience, which is enhanced when supervisees have a foundational knowledge of supervision theory and practice. To meet this end, this article is written as a direct personal message to students, explaining the basics of supervision models, processes, practices, tensions, and possible solutions to common supervision struggles. Although this article is written for students, we believe that its contents are equally relevant to supervisors.